Impact of electronic cigarette use and sleep duration, sleep issues and insomnia: a systematic review and meta-analysis - Sulthana, Huma; Jan, Asif; Verma, Amogh; Sah, Ranjana; Mehta, Rachana; Ullah, Aftab; Rahim, Abdur; Alqudimat, Mohammad R.; Ullah, Asmat (Frontiers in Public Health, 2025)
BackgroundThe increasing popularity of electronic cigarettes (e-cigarettes) has introduced new public health challenges and concerns. While promoted as safer alternatives to conventional tobacco and as tools for quitting smoking, e-cigarettes have raised alarm about possible long-term health consequences. This systematic review and meta-analysis sought to evaluate the association between electronic cigarette consumption and sleep disturbances.MethodsWe performed comprehensive searches in EMBASE, Web of Science, and PubMed up to September 18, 2024, to locate studies examining the link between e-cigarette use and sleep duration, sleep disorders, and insomnia. A meta-analysis was conducted to calculate pooled odds ratios (ORs). The quality of the studies was evaluated using the Newcastle-Ottawa Scale. Meta-analysis was performed using R software (Version 4.3).ResultsA total of 14 cross-sectional studies were included from 554 unique records screened. E-cigarette users exhibited a notably elevated risk of having shorter sleep duration compared to non-users, with a pooled odds ratio of 1.38 (95% CI: 1.24–1.55). Several studies reported that e-cigarette users also had higher odds of sleep disturbances, such as insomnia and reliance on sleep medications. Among adolescents, e-cigarette use was associated with a 33 to 61% increased risk of inadequate sleep.ConclusionE-cigarette use may be associated with sleep disturbances, including shorter sleep duration and increased sleep difficulties. Future long term longitudinal studies are warranted for better evidence.